Tiga Aspek dalam Pembelajaran Pendidikan Jasmani pada Masa Pandemi Covid-19 - Fatkhur Rozi; Setiorini Rahma Safitri; Ibdaul Latifah; Dewi Wulandari (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to analyze the aspects of safety, immunity, and faith in physical education learning at IAIN Salatiga. This study used a qualitative method with a phenomenological approach and used a case study design. The subjects of this study were lecturers and students of IAIN Salatiga who carried out physical education lectures in the odd semester of 2020/2021. The research instrument is the researcher himself using observation and documentation techniques in data collection. The data validity test in this study is utilizing data credibility test, transferability test, dependability test, and confirmability test. The results of this study indicate that the implementation of physical education lectures was carried out online during the Covid-19 Pandemic in IAIN Salatiga by utilizing youtube, whatsapp, and google classroom media. Furthermore, students are given physical fitness exercises independently by the lecturer. Besides, praying together before and after physical education lectures are held. This research concludes that the safety aspect has been carried out during the Physical Education lectures at IAIN Salatiga by implementing online lectures, the immune aspect is carried out through an independent fitness program, and the faith aspect is carried out by carrying out joint prayers.